Teamwork in Hospitality [viderecording] (Films Media Group, 2009)
This program helps students who are aiming for the hospitality industry understand why teamwork is vital to the success of an establishment, what its core principles are, and how it can be put into practice and strengthened. The video examines team structure, including both front-of-house and back-of house; basic teamwork concepts, including collaboration, morale, incentives, understanding individual roles, and identifying common goals; the importance of staff meetings and "handover" discussions; verbal, visual, and written communication techniques; and ways to solicit feedback from customers and staff.